Comparison of the Effect of Schema Therapy and Mindfulness Technique on Existential Anxiety in Individuals with Multiple Sclerosis - Din Parast, Omid; Rasouli, Narges; Ghotb, Seyed Iman (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The present study aimed to compare the effect of schema therapy and mindfulness technique on existential anxiety in individuals with multiple sclerosis. Methods and Materials: Based on its objective, the present study is of an applied type. The research design was quasi-experimental with a pre-test, post-test design with a control group. Participants were randomly assigned to two experimental groups and one control group. The statistical population of the study included all individuals with MS in Tehran. Using purposive sampling, individuals present in the MS Society were selected based on their pre-test scores on each variable and randomly assigned to three groups, including two experimental groups and one control group (15 individuals per group). The Good Existential Anxiety Scale was used to measure the research variables. Mindfulness training sessions were conducted according to Baer’s (2006) protocol, and schema therapy was based on the proposed protocol by Young et al. (2003). The intervention was implemented over 8 consecutive weeks, with each session lasting 90 minutes. In the inferential statistics section, covariance analysis was used to examine the effectiveness of the therapeutic methods. Findings: The results indicated that the impact of schema therapy and mindfulness technique on dimensions of existential anxiety (e.g., purposelessness of tasks, worthlessness of life’s meaning, inability to persuade others, disinterest in activities, and lack of responsibility towards others) was significant at the level of (p < 0.05). Conclusion: The results showed that there is a significant difference between the effectiveness of schema therapy and mindfulness technique in terms of their impact on existential anxiety in individuals with multiple sclerosis. The mindfulness technique was found to be more effective than schema therapy for individuals with multiple sclerosis.